Using Storytelling Technique To Teach Speaking For Tenth Graders Of Senior High School (RETAIN, 2020)
English has a significant part to play in our lives. It is one of the essential means which people from different countries can communicate and express ideas. English is being given and taught to students today, from elementary to university. Essentially, individuals need correspondence with others. To do this, they need language to communicate their inclination, thoughts, and wants to other people. Learning English means learning four major skills: listening, speaking, reading, and writing. Besides four language skills, it also learns three important components such as pronunciation, vocabulary, and grammar. This research aimed to describe (1) how the implementation of storytelling technique in students speaking skills and (2) how student’s response toward the implementation of storytelling technique. The research take place in SMAN 1 Bangsal. The observation was done in the classroom. The data was taken from both verbal and non-verbal activities and then it was in the form of fieldnotes. The result of this research can be concluded that using storytelling technique is effective than memorization since it provides learning vocabulary and grammatical in context rather than memorizing words in isolation. Keywords: storytelling, speaking